From Yalta to Thessaloniki — Nikolai Petrovich Krasnov (1864–1939), a Versatile Russian Architect - Mađanović, Milica (Actual Problems of Theory and History of Art, 2016)
Being the court architect in the service of the Russian Empire and the Kingdom of Yugoslavia and receiving commissions from the rich and the powerful, Nikolai Petrovich Krasnov actively influenced shaping of European public spaces. From Crimea to Greece, Krasnov’s distingueshing architecture contributed to the construction of visual identities throughout the south Eastern Europe. Academician at Saint-Petersburg Academy of Arts, he was one of the last architects of the Russian Imperial Court and the personal tutor of the Romanov princesses. Apparently, Krasnov’s artistic legacy has a significant value and deserves an international recognition. This paper draws attention both to his versatile architectural production and a turbulent life path. It presents the results of the author’s recent research. As the first paper on this architect, published in English, the article is aimed at the international popularization of Krasnov’s heritage.